Konsep Pengembangan Bahan Ajar Bahasa Arab bagi Peserta didik di Indonesia - Fauzana Annova (IAIN Madura, 2022)
Several researchers have carried out studies on the development of Arabic teaching materials before this. Unlike the previous ones, this research intends to describe the product of Arabic teaching materials for non-Arabic students in Indonesia. The focus of the study includes the principles, principles, and models of developing Arabic teaching materials. The research method is library research, namely by collecting data from source books, journals, and documents that are considered appropriate to the focus of this research analysis. The results of the study indicate that several principles need to be considered in the development of teaching materials, namely cultural and social principles, psychological principles, and linguistic and educational principles. Some of the principles in the development of Arabic teaching materials are scientific, paying attention to the development and needs of students, systematic, relevance or suitability, consistency, adequacy or adequacy, actual and contextual, flexible and comprehensive. The teaching material development model itself may refer to the following models: the Ismail Shinniy et al. model, the Chatibul Umam et al. model, the al-Fauzan model, and the Abdulah Hamid model..